Causes of delay in proper treatment of patients with undescended testis - Student, Rahil Ghahramani; Mohammad Kermani-Alghoraishi; Nooshin Moosavi; Soheil Benrazavi; Abbas Modir; Seyyed Mostafa Shiryazdi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Undescended testis (UDT) is the most common endocrine disorder in male children. Delayed diagnosis and treatment of UDT lead to complications such as infertility, malignancy and testis rotation. Objective: The aim of this study was to evaluate the causes of delay in proper treatment of patients with undescended testis in our population.Materials and Methods: An observational, descriptive, cross sectional study of 143 male patients, who applied to Shahid Sadoughi University Hospitals for orchiopexy operation was performed. The maximum recommended age for orchiopexy was 18 months.Results: The mean age at referral was 5.34 years. Only 44 (30.8%) cases were operated on before the age of 18 months. The most common reasons of delay in treatment were absence of early diagnose (42.5%), parent's unawareness of surgery necessity and its complications associated (33.7%) and parent's disregard (23.5%). Only 19.6% of patients were diagnosed at born in the hospital. 49% of parents had the correct information for proper operation age and 40.6% of them had enough information about necessity of surgery and side effects of disease. Parent's literacy, place of living and type of cryptorchidism had no significant relation with delay diagnosis (p> 0.05).Conclusion: These results revealed that late diagnosis by physician and lack of insight of parents are the main reasons in delayed diagnosis and treatment of UDT. Therefore, education of parents and careful physical examination of the babies at birth and regular follow-up until 18 months can prevent the delay in diagnosis.